Comparative Study on the Extraction of Crude Fucoidan from Brown Seaweed using Conventional, Microwave and Ultrasound-Assisted Methods - Dwijayanto, Afif; Al-Yousefi, Ahmed Mahmood Abdulhameed Abdullah; Puspasari, Ifa; Markom, Masturah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Brown seaweeds are rich in fucoidan, a sulfated polysaccharide with antimicrobial, immunomodulatory, antioxidant, and anticancer properties. The brown algae Sargassum sp. has not been thoroughly investigated for fucoidan extraction using various techniques and evaluations of their effects on extraction yield and its structural properties. The purpose of this study was to compare the structural characteristics and extraction yield of fucoidan from Sargassum sp. using conventional, microwave, and ultrasonic-assisted extraction methods. The results showed that a slightly higher yield was obtained by using the ultrasonic-assisted extraction method (2.772%) followed by the microwave-assisted extraction method (2.494%) and conventional extraction method (2.399%). However, the IC50 values for antioxidants were found to be lower (less value is preferable) for crude fucoidan obtained by microwave-assisted extraction method (175 ?g/ml) than for conventional (195 ?g/ml) and ultrasound-assisted extraction methods (230 ?g/ml). The crude fucoidan obtained from the three different extraction methods showed moderate antioxidant strength Contribution to Sustainable Development Goals (SDGs)SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionDG 14: Life Below Water